Examining Leadership Stress Among School Principals: Insights from Stress Sources and Coping Strategies - Gilang Gumilang Dawous; Djama'an Satori; Munir Munir; Nugraha Suharto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This study examines the types of stress, sources of stress, coping strategies, and their impacts on school principals' leadership. A descriptive quantitative approach was employed, with data collected from 325 elementary school principals in Garut Regency using a semantic differential scale questionnaire. Path analysis revealed that stress sources, such as workload, interpersonal conflicts, and limited resources, have a significant impact on stress outcomes, while stress types and coping strategies show weaker but measurable effects. Principals predominantly adopted problem-focused strategies, such as task prioritization and time management, and emotion-focused strategies, including seeking peer support and practicing self-care. These strategies were shown to moderate stress impacts, albeit to a limited extent. The study underscores the critical need for targeted interventions in stress management, focusing on equipping principals with effective coping mechanisms to enhance their productivity and well-being.